P18. Pattern of 'resting-state' functional hyperconnectivity in Amyotrophic lateral sclerosis reflects neuropathological disease stages. Issue 8 (August 2015) - Röll, I.; Gorges, M.; Müller, H.-P.; Lulé, D.; Ludolph, A.C.; Kassubek, J.
<x xml:space="preserve">Abstract</x> Background Autopsy-controlled studies in Amyotrophic lateral sclerosis (ALS) proposed a 4-stage sequential spreading of the underlying TDP-43 pathology (Brettschneider et al., 2013). Recently the in vivo transfer of the neuropathological stages by use of tract of interest-based diffusion-tensor-imaging (DTI) has been performed (Kassubek et al., 2014). Based upon the DTI findings, we have expanded the imaging approach by complementary investigation of ifc-fMRI in order to trace the pathology spreading in well-defined intrinsic functional connectivity networks (ICNs). Methods We used a 3.0T resting state-fMRI protocol for 76 ALS patients and 28 healthy controls. The preprocessing followed standardized procedures including motion correction, MNI normalization, spatial filtering, temporal linear detrending and bandpass filtering. ICNs were identified utilizing the seed-based approach (Gorges et al., 2014). These ICNs comprised the motor (neuropathological stage 1), frontoparietal, frontal executive and brainstem (stage 2), basal ganglia (stage 3), and hippocampal (stage 4) networks; we used the visual ICN as reference. Results ALS patients compared with healthy controls demonstrated a large-scale pattern of increased functional connectivity (hyperconnectivity) in all networks with the exception of the reference network. More specifically, the hyperconnectivity pattern extended spatially into adjacent brain structures following the neuropathological spreading. The hyperconnectivity in stage 1 extended into frontal areas, in stage 2 into prefrontal and postcentral areas, in stage 3 into prefrontal and postcentral areas, and in stage 4 within the hippocampal formation. Moreover, the disease stages as observed in vivo by DTI significantly correlated with increasing functional connectivity in the ICNs. Conclusion Ifc-fMRI provides a promising approach to functionally trace pathological spreading in ALS. As recently suggested (Douaud et al., 2011), the loss of the inhibitory influence may be most likely attributable to the pattern of hyperconnectivity in ALS. With increasing stages of disease, hyperconnectivity seems to spread sequentially into more frontal and postcentral regions following the neuropathological spreading.